2013
DOI: 10.1007/s00412-013-0441-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and beyond: the role of mammalian class I lysine deacetylases

Abstract: The Rpd3-like members of the class I lysine deacetylase family are important regulators of chromatin structure and gene expression and have pivotal functions in the control of proliferation, differentiation and development. The highly related class I deacetylases HDAC1 and HDAC2 have partially overlapping but also isoform-specific roles in diverse biological processes, whereas HDAC3 and HDAC8 have unique functions. This review describes the role of class I KDACs in the regulation of transcription as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 129 publications
(182 reference statements)
1
97
0
Order By: Relevance
“…Deletion of either Hdac1 or Hdac2 in a variety of tissues/cell types, including the heart, brain, endothelial cells, smooth muscle, and neural crest cells, ES cells, fibroblasts, B cells, thymocytes, keratinocytes, and various cell lines causes no or only mild effects. 9,16,28 Likewise, deletion of either Hdac1 or Hdac2 does not evoke an obvious effect on oocyte development to the full-grown oocyte stage. 43 Deletion of both Hdac1 and Hdac2, however, results in infertility due to oocyte development arresting at the secondary follicle stage, which is accompanied by mis-regulation of histone modifications, a significant reduction of global transcription, and an increased incidence of apoptosis.…”
Section: Hdac1 and Hdac2 Regulate Oocyte Development Through Transcrimentioning
confidence: 96%
See 2 more Smart Citations
“…Deletion of either Hdac1 or Hdac2 in a variety of tissues/cell types, including the heart, brain, endothelial cells, smooth muscle, and neural crest cells, ES cells, fibroblasts, B cells, thymocytes, keratinocytes, and various cell lines causes no or only mild effects. 9,16,28 Likewise, deletion of either Hdac1 or Hdac2 does not evoke an obvious effect on oocyte development to the full-grown oocyte stage. 43 Deletion of both Hdac1 and Hdac2, however, results in infertility due to oocyte development arresting at the secondary follicle stage, which is accompanied by mis-regulation of histone modifications, a significant reduction of global transcription, and an increased incidence of apoptosis.…”
Section: Hdac1 and Hdac2 Regulate Oocyte Development Through Transcrimentioning
confidence: 96%
“…The reader is referred to several excellent reviews discussing the physiological role of HDAC1 and HDAC2. 8,9,16,28,39 Here we summarize and discuss the results of experiments using conditional mutant mice in combination with RNA interference (RNAi) to dissect the roles of HDAC1 and HDAC2 in oocytes and preimplantation embryos.…”
Section: Structure and Complexes Of Mammalian Hdac1 And Hdac2mentioning
confidence: 99%
See 1 more Smart Citation
“…Histone deacetylases (HDACs) exhibit limited substrate specificity and rely on transcription factors with sequence-specific DNAbinding and/or chromatin-binding activities for their targeting specificity. Among 11 known Zn 2+ -dependent HDACs in mammals, only HDAC1, HDAC2, and HDAC3 are constitutively nuclear, regulating the transcription of a broad array of genes that impact fundamentally on cellular physiology and organism development (1)(2)(3). These HDACs are commonly found in multiprotein corepressor complexes, with the closely related HDAC1 and HDAC2 partitioning broadly into the Sin3L/Rpd3L, Sin3S/ Rpd3S, NuRD (nucleosome remodeling and deacetylase), and CoREST (corepressor of REST transcription factor) complexes, whereas HDAC3 is found exclusively in SMRT/NCoR (silencing mediator of retinoid and thyroid hormone receptor/nuclear receptor corepressor) complexes.…”
mentioning
confidence: 99%
“…We cannot exclude, however, the importance of nonnuclear HDACs in modulating pancreatic recovery through the posttranslational regulation of nonhistone proteins. 49 VPA, however, primarily targets HDAC1 and other nuclear HDACs, and it does not appear to affect cytoplasmic HDACs. 50 The higher HDAC expression we observed during pancreatic recovery is similar to what was reported during pancreatic development by Haumaitre et al 16 They also found that HDACi shifted the expansion of pancreatic precursors in a rat embryonic explant from an acinar to b-cell phenotype, suggesting that HDACs play a role in the maturation of the embryonic precursors into acinar cells.…”
Section: Discussionmentioning
confidence: 95%